Advances in Organic Coatings 2018 - Deflorian, Flavio (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The recent huge developments in nanotechnology and surface science are allowing the production of multifunctional coatings materials combining different properties: corrosion-protective actions, aesthetic functions, hydrophobic properties, self-healing abilities, etc. Moreover the increasing attention to environmental issues is driving the development of new systems, joining advanced performance with high sustainability, which can be better understood using new highly efficient experimental techniques. This frame is inducing us to consider the advances in organic coatings (the skin of materials) as one of the most interesting and promising innovation fields in material science and technology, with important consequences, not only considering fundamental aspects in science, but also for industrial applications, positively affecting everyday life. The aim of this Special Issue is to provide an update of the most advanced research in this area, showing the innovation trends and promoting further research for better properties of new coating materials.